Epigenetics of cancer drug resistance - Sayandeep Mukherjee; Ronit Dey; Subhabrata Guha; Nabendu Murmu; Gaurav Das (Academia Biology)
One of the major causes due to cancer-related death is metastasis. The major factors contributing to metastasis of cancer cells are epithelial–mesenchymal transition and cancer stem cells. There are multiple evidences which suggest that malfunction of epigenetic regulation in functioning of a gene is directly related to the development of cancer. The capability to change or reprogram the landscape of epigenetics in the epigenome of cancer is the most promising and guaranteed targeted therapy that leads to the reversibility of drug resistance and new modalities of treatment in cancer. This review clearly focuses on various epigenetic modifications which leads to antitumor drug resistance and how epigenetic modifiers can reverse drug resistance.